CD147 contains different bioactive epitopes involving the regulation of cell adhesion and lymphocyte activation - Chiampanichayakul S. (2014)
CD147 is a leukocyte surface molecule which belongs to the immunoglobulin superfamily. It is broadly expressed on various cell types and is a lymphocyte activation-associated molecule. In order to study the function of CD147, five CD147 monoclonal antibodies (mAbs) were generated: M6-2F9; M6-1D4; M6-1F3; M6-1B9; and M6-1E9. Biochemical characterizations and cross-blocking experiments indicated that M6-1B9 and M6-1E9 recognize the same or contiguous epitopes on CD147. By employing COS transfectants expressing CD147 membrane-distal domain (domain 1) and membrane-proximal domain (domain 2), mAbs M6-2F9, M6-1D4, M6-1B9, and M6-1E9 were shown to recognize epitopes located on domain 1 of the molecule. Functional studies indicated that engagement of CD147 by mAbs M6-1B9 and M6-1E9 strongly inhibited lymphocyte proliferation induced by a CD3 mAb. In contrast, mAbs M6-2F9, M6-1D4, and M6-1F3 induced U937 homotypic cell aggregation. The results indicate that CD147 contains at least two bioactive domains. Epitopes responsible for induction of cell aggregation are different from those regulating lymphocyte activation.